Shaping ability of non-adaptive and adaptive core nickel–titanium single-file systems with supplementary file in ribbon-shaped canals analysed by micro-computed tomography - Chinchiyanont P. (2023)
This study compared shaping ability between two single-file systems and before/after using supplementary file in untouched area, volume of removed dentin, maximum cut depth (the highest cut depth by main file) and remaining thinnest dentin (the thinnest root dentin after preparation). Ribbon-shaped distal canals of mandibular molars were prepared with non-adaptive core (WaveOne Gold) or adaptive core (XP-endo Shaper) files (n = 15/group) and additionally prepared with a supplementary file (XP-endo Finisher), and the shaping ability was investigated using micro-computed tomography. XP-endo Shaper group demonstrated significantly less overall untouched area than WaveOne Gold group (38.21 ± 6.98% vs. 47.68 ± 9.16%) (p < 0.05). No significant difference was detected between XP-endo Shaper and WaveOne Gold groups in volume of removed dentin (1.85 ± 0.53 vs. 1.66 ± 0.33 mm3), maximum cut depth (0.10–0.28 vs. 0.10–0.29 mm) and remaining thinnest dentin (0.66–0.80 vs. 0.78–0.88 mm). Supplementary XP-endo Finisher treatment significantly decreased untouched area (11%–23% reduction) (p < 0.05) with minimally cut root dentin (0.01–0.02 mm).